Penerapan Model Pembelajaran Cooperative Scriptyang Dipadu denganThink Pair Share untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPA Biologi - Rahmawati, Lidya; Nuraida, Dede (Universitas Sebelas Maret, 2018)
This research is based on the result of interview with science teacher in SMP Negeri 3 Semanding it is known that the learning method used by teachers in SMP Negeri 3 Semanding Tuban still using conventional learning method that is teacher-centered learning method. So that results in low student learning outcomes. Responding to this the researchers took the initiative to use Cooperative Script learning model combined with Think Pairs Share to overcome the above problems. This research is a Classroom Action Research (PTK). This classroom action research is conducted with 2 cycles, namely cycle I and Cycle II. This research was conducted at SMPN 3 Semanding class VII-C on science subject Biology subject of environmental pollution in academic year 2017/2018 with subject of research is student of class VII-C with total of 22 students consist of 12 male students and 10 students women. The results of the research implementation as much as two cycles obtained increased learning outcomes by 22.73%, increased teacher activity by 21.25%, and increased student activity by 22.5%. Thus it can be concluded that the implementation of Cooperative Script learning model combined with Think Pair Share can increase learning outcomes, teacher activity and student activities.